PENGARUH PEMBERIAN PAKAN ALAMI CACING Tubifex sp. TERHADAP PERTAMBAHAN PANJANG DAN BOBOT IKAN ZEBRA (Branchyndanio rerio): THE EFFECT OF NATURAL FEEDING Worms Tubifex sp. TOWARDS THE LENGTH AND WEIGHT OF ZEBRA FISH (Branchyndanio rerio) - Asep Rachmat Pratama (Jendela ASWAJA, 2021)
One of the ornamental fishes which has a fairly good development prospect is zebra fish (Branchyndanio rerio). In the maintenance of zebra fish is needed special treatment in handling the fish larvae. The purpose of this study was to determine the effect of natural feeding on the Tubifex sp. silkworm to increase the length and weight of zebra fish larvae. This study contained 2 treatments, namely treatment A (feeding pellets in the morning and evening) and treatment B (feeding the Tubifex sp. silkworm in the morning and evening). Each treatment was carried out with 3 replications. Pellet feed and Tubifex sp. silkworm were given each ad libitum for 30 days. The results of this study showed that the percentage of fish seed increase in treatment B experienced a significant increase rather than just given pellet feed (Treatment A). For 30 days, the natural feeding of the Tubifex sp. in the morning and evening, fish larvae experienced a length increase of 13.78% and weight of 106.48%. This result is very different from fish larvae which were only given pellet feed in the morning and evening, which is only 12.31% for their weight and their length is fixed. The conclusion of this study is the natural feeding of Tubifex sp. have a significant effect on the length and weight of zebra fish larvae